Studi Penggunaan Antipsikotik dan Efek Samping pada Pasien Skizofrenia di Rumah Sakit Jiwa Sambang Lihum Kalimantan Selatan - Mawar Dwi Yulianty; Noor Cahaya; Valentina Meta Srikartika (Jurnal Sains Farmasi & Klinis, 2017)
Based on RISKESDAS 2013, schizophrenia prevalence in South Kalimantan is 1.4 per one thousand population. The main therapy for schizophrenia is anti-psychotic medication. A variety of side effects arise from the use of antipsychotic drugs including extrapyramidal syndrome and metabolic syndrome. The aim of the study was to evaluate the prescription pattern and side effects of antipsychotic drugs in patients with schizophrenia at Sambang Lihum Psychiatric Hospital, South Kalimantan, Indonesia. The type of this study was non-experimental observation with prospective data collection. Population in this study was all of the schizophrenia inpatients in February 2016 who met the inclusion criteria. The data were collected from 59 patients. The results showed that anti-psychotics combination therapy was the most widely used medications (90.6%), in which the combination of haloperidol-clozapine was the most frequent one (26.04%). The side effects commonly observed were extrapyramidal syndrome (98.3%); orthostatic hypotension (86,4%); anticholinergic effect (76.3%); sedation (44.1%); nausea / vomiting (27.1%); diarrhea (27.1%); insomnia (16.9%); loss of appetite (10.2%); red-itchy rashes (6.8%); anorexia (5.1%); frequent urination (5.1%); decreased consciousness (1.7%), shortness of breath and cough (1.7%); impairment of Hb (1.7%); increase in AST (1.7%); increase in ALT (1.7%); and foaming from nose (1.7%).